Rasio Tepung Kulit Singkong Dengan Ikan Tongkol Terhadap Sifat Organoleptik Bakso Tepung Kulit Singkong Ikan Tongkol (Bakso Kingkong) - Selvi Indrawati; IKetut Swirya Jaya; Igde Narda Widiada; AASP Chandradewi (Poltekkes Kemenkes Mataram, 2017)
Background. Shifting diet of people in Indonesia to change, to foods high in fat and low in fiber. Leather Cassava is a high-fiber foods. Leather Cassava can be used in the manufacture of fish balls. Another ingredient in the manufacture of starch ie meatballs. Pratiwi Research, (2013) stated that the nutrient content of crude fiber contained in tapioca is 0% so that the necessary ingredients of nutrient-rich foods crude fiber in making the meatballs then selected skin cassava. Research Methods. was implemented using the design of experimental studies with a completely randomized design (CRD) of the ratio factor flour cassava peel with tuna 10%: 90%, 20%: 80%, 30%: 70%, 40%: 60% and 50 %: 50%. The treatment was repeated 3 times. The parameters observed organoleptic properties (color, smell, taste and texture). Data were analyzed using Duncan test. The results showed that the ratio of cassava flour shell with tuna significant effect on the color, smell, taste and texture of Meatballs. Colors get scores of panelists from 2.96 to 4.08, a score value odors from 2.96 to 3.56, a score value of flavor from 2.20 to 3.72, and texture scores from 2.20 to 3.20. The conclusion that the treatment of the most favored in terms of color, taste, smell and texture that treatment with t1 (10%: 90%). T1 treatment (10%: 90%) is a product that is recommended because it has the organoleptic properties of the most preferred.